Statistics on the Industry Structure of the Russian Economy and its Optimization Model - O. V. Morozov; M. A. Vasiliev (Статистика и экономика)
This article describes the results of econometric research and optimization of the industry structure of the Russian economy. The results of modern domestic research on this topic show that the task of establishing theoretically justified quantitative criteria for optimizing the structural composition of multicomponent (discrete) social systems remains beyond due attention and not only should, but can be solved. Therefore, the purpose of this study is to determine the optimal size, to establish a measure of a harmonious combination of the sectoral components of the domestic economy and, on their basis, to develop an actual orientation of the structural economic policy of the Russian state for the foreseeable future.Materials and methods. The theoretical foundations of the study are developed on the basis of the authors’ preferences regarding the results of conceptual and applied developments of domestic scientists in the field of structural analysis of systems. The methodological basis of the research consists of works on the structural organization of systems, the concept of structural harmony of systems, the dialectic of harmony, the modular theory of society, and econometrics. The analysis of parameters (indicators) of the component composition of the domestic economy was carried out on the basis of statistical data of ROSSTAT for 2018. The assessment of the export-import potential of the domestic economy is based on statistical data on the cost of output of goods and services for 2014-2018. Econometric methods of processing the initial data and tabular methods of visualizing the results of the study were used. Standard Microsoft Office application software packages were used to solve the research tasks.Results. The theoretical foundations, the procedure and algorithms for studying the structure of multicomponent (discrete) systems are presented. The criterion (maximizing the structural potential of the development of the system under study) is determined and a quantitative model for optimizing their structure is constructed. On the basis of the model, the optimal scales of the structural components (branches) of the domestic economy are determined. According to the statistics for 2018, reflecting the resource capacity (employment, fixed assets, number of organizations) and the results of activities (value added, investment activity), econometric calculations of the relative (in comparison with the entire economy) sizes of the Russian economy sectors were made. Comparison of actual and model (optimal) indicators of the magnitude of domestic industries as a way to detect non-optimality (the discrepancies) of its structure, shows the path of transition from its actual status to “the best” structure which describes a quantitative model of optimal combination of scale of its industries.Conclusion. Based on the quantitative model of optimization of the industry structure, the unbalanced nature of the industry structure, the need for harmonization of the industry composition and, thus, the presence of structural reserves for economic growth of the Russian economy are shown. Optimization of the scale of industries is the formation of structural conditions for a more efficient functioning of the Russian economy; it can be recognized as a macroeconomic condition and a strategic reserve for the economic growth.